Polygenic risk for schizophrenia predicting social trajectories in a general population sample - Saarinen Aino; Hietala Jarmo; Lyytikäinen Leo-Pekka; Hamal Mishra Binisha; Sormunen Elina; Lavonius Veikka; Kähönen Mika; Raitakari Olli; Lehtimäki Terho; Keltikangas-Järvinen Liisa (Cambridge University Press, 2026)
Background
We investigated (a) whether polygenic risk for schizophrenia predicts different trajectories of social development among those who have not developed psychoses and (b) whether possible associations are PRSSCZ-specific or evident also for any polygenic risk for mental disorders, e.g. for major depression.
Methods
Participants came from the population-based Young Finns Study (n = 2377). We calculated a polygenic risk score for schizophrenia (PRSSCZ) and for major depression (PRSDEP). Diagnoses of psychotic disorders were derived from the hospital care register. Social development from adolescence to middle age was measured by (a) perceived social support from friends, family, and a close other, (b) perceived sociability, and (c) family structure (partnership status, number of children, age of first-time parenthood).
Results
Among those without manifest psychoses, high PRSSCZ predicted lower experienced support from friends (B = −0.04, p = 0.009–0.035) and family (B = −0.04, p = 0.009–0.035) especially after early adulthood, and also lower perceived sociability (B = −0.05, p = 0.010–0.026). PRSSCZ was not related to family structure. PRSDEP did not predict any domain of social development.
Conclusions
Individuals at high PRSSCZ (not converted to psychosis) seem to experience a lower preference to be with others over being alone. Individuals with high (v. low) PRSSCZ seem to have a similar family structure in terms of partnership status or number of children but, nevertheless, they experience less support from their family. Among those not converted to psychosis in a typical age period, high PRSSCZ may predict a ‘later risk phase’ and reduced functional resilience when approaching middle age.